Electronic properties and circuit applications of networks of electrochemically exfoliated 2D nanosheets - Carey, Tian; Coleman, Jonathan; Wells, Rebekah (My University, 2025)
High aspect-ratio 2D materials are promising for solution-processed electronics, yet the factors controlling exfoliation remain unclear and relatively few solution-processed networks have been electrically characterized. Here we combine theory and experiment to show that electrochemical exfoliation of layered crystals with sufficient stiffness-anisotropy (in-plane/out-of-plane Young’s modulus ratio >1.7) yields high aspect-ratio nanosheets with intrinsic mobilities μNS = 20–75 cm²V⁻¹s⁻¹ across transition metal dichalcogenides and related alloys. Impedance spectroscopy indicates that solution-deposited networks can achieve junction-to-nanosheet resistance ratios (RJ/RNS) as low as ~3, supporting theoretical predictions that μNS/μNet = RJ/RNS + 1 and suggesting that further reductions in RJ will increase μNet toward the nanosheet limit (μNS). These networks display n-type, p-type, and ambipolar behaviour, with on/off ratios up to 10⁵ and mobilities μNet = 13 cm²V⁻¹s⁻¹. Here, we show that such high-performing 2D materials enable functional solution-processed circuits, including inverters, buffers, a 4-bit digital-to-analog converter, and a circuit capable of encoding and decoding 7-bit ASCII messages.
PUBLISHED
Keywords: Nanoscience & Materials; Materials Sciences; Physics